2012
DOI: 10.4049/jimmunol.1101764
|View full text |Cite
|
Sign up to set email alerts
|

MF59 and Pam3CSK4 Boost Adaptive Responses to Influenza Subunit Vaccine through an IFN Type I-Independent Mechanism of Action

Abstract: The innate immune pathways induced by adjuvants required to increase adaptive responses to influenza subunit vaccines are not well characterized. We profiled different TLR-independent (MF59 and alum) and TLR-dependent (CpG, resiquimod, and Pam3CSK4) adjuvants for the ability to increase the immunogenicity to a trivalent influenza seasonal subunit vaccine and to tetanus toxoid (TT) in mouse. Although all adjuvants boosted the Ab responses to TT, only MF59 and Pam3CSK4 were able to enhance hemagglutinin Ab respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
87
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 34 publications
10
87
0
Order By: Relevance
“…8). These data are consistent with previously published reports that show an increase in IP-10 and IL-1Ra expression in response to MF59 (Caproni et al, 2012;Mosca et al, 2008;Seubert et al, 2008), as well as increased CRP and IP-10 expression in response to influenza vaccination (Christian et al, 2011;Nakaya et al, 2011;Obermoser et al, 2013). IL-2Ra and sTNFRII remained at baseline levels in the serum, with no difference observed between the adjuvanted and non-adjuvanted animals in response to intramuscular immunisation.…”
Section: Inter-and Intra-assay Variationsupporting
confidence: 82%
“…8). These data are consistent with previously published reports that show an increase in IP-10 and IL-1Ra expression in response to MF59 (Caproni et al, 2012;Mosca et al, 2008;Seubert et al, 2008), as well as increased CRP and IP-10 expression in response to influenza vaccination (Christian et al, 2011;Nakaya et al, 2011;Obermoser et al, 2013). IL-2Ra and sTNFRII remained at baseline levels in the serum, with no difference observed between the adjuvanted and non-adjuvanted animals in response to intramuscular immunisation.…”
Section: Inter-and Intra-assay Variationsupporting
confidence: 82%
“…Not only an increased cellularity of dLNs but also an enhanced activation of various cell types including B cells, T cells, migratory DCs, NK cells and NKT cells following the adjuvant injection was observed. Similar phenomenon was observed after the use of a TLR agonist such as R848 43 suggesting that RNAdjuvant 44,45 Using a murine model of HPV-16-induced cervical cancer we demonstrated that vaccination with low doses of the previously described HPV-E7-derived peptide containing both, a CTL epitope (E7 [49][50][51][52][53][54][55][56][57] ) and a Th epitope, 24 led to a complete eradication of established tumors in combination with RNAdjuvant V R . Similar results were obtained by Zwaveling and colleagues using E7 peptide combined with CpG.…”
Section: Rnadjuvantmentioning
confidence: 57%
“…The HI assay was carried out on individual sera taken 2 wk after the second immunization, as described elsewhere (17).…”
Section: Methodsmentioning
confidence: 99%
“…Four mice per group were killed 2 wk after immunization, and spleens were collected to assess the frequency and phenotype of Ag-specific CD4 + /CD44 + T cells induced by vaccination. The assay was performed as described elsewhere (17).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation